2011
DOI: 10.1603/ec11077
|View full text |Cite
|
Sign up to set email alerts
|

Rainfastness and Residual Activity of Insecticides to Control Japanese Beetle (Coleoptera: Scarabaeidae) in Grapes

Abstract: Field-based bioassays and residue profile analysis were used to determine the relative toxicity, rainfastness, and field degradation over time of five insecticides from five insecticide classes on adult Japanese beetles, Popillia japonica Newman (Coleoptera: Scarabaeidae), in grapes, Vitis labrusca L. Bioassays assessed Japanese beetle condition as alive, knockdown, or immobile when exposed for 24 h or 7-d field-aged residues of phosmet, carbaryl, bifenthrin, thiamethoxam, or indoxacarb after 0, 12.7, or 25.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
3
16
0
1
Order By: Relevance
“…In a previous experiment, the insecticides phosmet and carbaryl were tested on Japanese beetles under identical rainfall conditions, but on grape (Vitis labrusca L.) leaves (Hulbert et al 2011) and in this experiment we observed similar efÞcacy patterns. The differences observed between the two studies are likely because of differences between in the physical characteristics of grape and blueberry leaves.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In a previous experiment, the insecticides phosmet and carbaryl were tested on Japanese beetles under identical rainfall conditions, but on grape (Vitis labrusca L.) leaves (Hulbert et al 2011) and in this experiment we observed similar efÞcacy patterns. The differences observed between the two studies are likely because of differences between in the physical characteristics of grape and blueberry leaves.…”
Section: Discussionsupporting
confidence: 74%
“…Studying the efÞcacy of older and newer and reduced risk insecticides after rainfall could decrease unnecessary insecticide reapplication and the associated costs and risks. Hulbert et al (2011) showed that the insecticides bifenthrin, thiamethoxam, and indoxacarb were all resistant to 12.7 and 25.4 mm of rainfall against Japanese beetle adults when sprayed on grapes, while other insecticides (phosmet and carbaryl) had signiÞcantly diminished efÞcacies after rainfall. It is important for a grower to be able to determine whether an insecticide spray is warranted after rainfall.…”
mentioning
confidence: 99%
“…Rainfall wash-off tests have been used in rain fastness and rainfall tenacity studies of several plant protection substances: foliar deposits of commercial formulations of diflubenzuron (Sundaram and Sundaram 1994), carbaryl (Willis et al 1996), chlorothalonil (Wauchope et al 2004), phosmet (Hulbert et al 2011), glyphosate commercial formulations (Gannon and Yelverton 2008), bio-herbicides (Boyette et al 2012), and fungicides such as dimethomorph, chlorothalonil, and mepanipyrim fungicides (Choi et al 2009). The influence of surfactants on the tenacity of tribenuron-methyl (Pannacci et al 2010), the sticker adjuvants based on organosilicone/latex added to fungicides (Gaskin and Steele 2009), and the effect of seed oil ethoxylate surfactants on the tenacity of the mancozeb (Hunsche et al 2008) were also studied using rainfall tests.…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento da infl uência das precipitações sobre a efi cácia dos inseticidas é de suma importância (HULBERT et al, 2011). Entretanto, os resultados do efeito da precipitação sobre a efi ciência do inseticida clorantraniliprole não podem Tabela 1 -Efeito do tempo de aplicação de precipitação artificial, em plantas de soja tratadas com o inseticida clorantraniliprole, sobre a mortalidade de lagartas de Anticarsia gemmatalis.…”
Section: Resultsunclassified